Phylogenetic relationships of cone snails endemic to Cabo Verde based on mitochondrial genomes. Issue 1 (December 2017) - Abalde, Samuel; Tenorio, Manuel; Afonso, Carlos; Uribe, Juan; Echeverry, Ana; Zardoya, Rafael
Abstract Background Due to their great species and ecological diversity as well as their capacity to produce hundreds of different toxins, cone snails are of interest to evolutionary biologists, pharmacologists and amateur naturalists alike. Taxonomic identification of cone snails still relies mostly on the shape, color, and banding patterns of the shell. However, these phenotypic traits are prone to homoplasy. Therefore, the consistent use of genetic data for species delimitation and phylogenetic inference in this apparently hyperdiverse group is largely wanting. Here, we reconstruct the phylogeny of the cones endemic to Cabo Verde archipelago, a well-known radiation of the group, using mitochondrial (mt) genomes. Results The reconstructed phylogeny grouped the analyzed species into two main clades, one includingKalloconus from West Africa sister toTrovaoconus from Cabo Verde and the other with a paraphyleticLautoconus due to the sister group relationship ofAfriconus from Cabo Verde andLautoconus ventricosus from Mediterranean Sea and neighboring Atlantic Ocean to the exclusion ofLautoconus endemic to Senegal (plusLautoconus guanche from Mauritania, Morocco, and Canary Islands). WithinTrovaoconus, up to three main lineages could be distinguished. The clade ofAfriconus included four main lineages (named I to IV), each further subdivided into two monophyletic groups. The reconstructed phylogeny allowed inferring the evolution of the radula in the studied lineages as well as biogeographic patterns. The number of cone species endemic to Cabo Verde was revised under the light of sequence divergence data and the inferred phylogenetic relationships. Conclusions The sequence divergence between continental members of the genusKalloconus and island endemics ascribed to the genusTrovaoconus is low, prompting for synonymization of the latter. The genusLautoconus is paraphyletic.Lautoconus ventricosus is the closest living sister group of genusAfriconus . Diversification ofAfriconus was in allopatry due to the direct development nature of their larvae and mainly triggered by eustatic sea level changes during the Miocene-Pliocene. Our study confirms the diversity of cone endemic to Cabo Verde but significantly reduces the number of valid species. Applying a sequence divergence threshold, the number of valid species within the sampledAfriconus is reduced to half.